2019
DOI: 10.1186/s12967-019-1895-2
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 drives the epithelial–mesenchymal transition in non-small-cell lung cancer through the Wnt/β-catenin pathway

Abstract: Background The distant metastasis of cancer cells is a risk factor for tumor lethality and poor prognosis in non-small-cell lung carcinoma (NSCLC). Increased SOX9 expression has been associated with clinical stage and poor prognosis in NSCLC, but the molecular mechanisms by which SOX9 promotes metastasis in NSCLC are still unknown. Methods The relationship between SOX9 expression and T, N, M classification was assessed using the χ 2 test and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 32 publications
(34 reference statements)
3
76
0
Order By: Relevance
“…42,49 Furthermore, most studies showed that βcatenin suppression could inhibit fibrosis. 23,28,46 Based on our results, showing that GSK-3β is regulated and phosphorylated by SOX9 and a recent study demonstrating that β-catenin, a downstream effector of SOX9, drove epithelial to mesenchymal transition in non-smalllung cancer, 25 we next explored the effects of miR-145 and SOX9 on the β-catenin pathway in CFs. We found that SOX9 and β-catenin were elevated in hypoxic CFs, both of which exhibited enhanced nuclear localization.…”
Section: Discussionmentioning
confidence: 97%
“…42,49 Furthermore, most studies showed that βcatenin suppression could inhibit fibrosis. 23,28,46 Based on our results, showing that GSK-3β is regulated and phosphorylated by SOX9 and a recent study demonstrating that β-catenin, a downstream effector of SOX9, drove epithelial to mesenchymal transition in non-smalllung cancer, 25 we next explored the effects of miR-145 and SOX9 on the β-catenin pathway in CFs. We found that SOX9 and β-catenin were elevated in hypoxic CFs, both of which exhibited enhanced nuclear localization.…”
Section: Discussionmentioning
confidence: 97%
“…Several genes connected with ESR1 have been associated with breast cancer stemness. For example, we previously reported the suppressive role of FOXA1 on breast cancer stemness [17]; SOX9 is as a stem cell factor [18] that drives the epithelial mesenchymal transition (EMT) in non-small cell lung cancer through Wnt pathway [19] and maintains human breast luminal progenitor and breast cancer stem cells through SOX9 mediated signaling [20], and both the SOX9/FXYD3/SRC [21] and the SOX9/SOX2 [20] axes are critical for breast cancer stem cell functionalities; PLA2G7 is associated with ER negativity in clinical breast cancer samples and regulates EMT in vitro [22]. The prognostic values of several markers have been reported, including PTPN6 and KRT19 in breast cancers [23][24][25], EPPK1 in non-small cell lung cancers [26], SERPINB5 in colorectal cancers [27], and NCCRP1 in squamous cell carcinoma [28].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has suggested that SOX9 may regulate the Wnt/β-catenin signaling pathway during tumorigenesis. [21][22][23][24] We therefore, detected whether there is a similar regulatory network in EC.…”
Section: Overexpression Of Sox9 Recovers Proliferation Of Cells Supmentioning
confidence: 99%